2023
DOI: 10.1038/s41419-023-05760-w
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla Protein drives stemness and tumor initiation in ovarian cancer

Abstract: Ovarian cancer (OC) displays the highest mortality among gynecological tumors, mainly due to early peritoneal dissemination, the high frequency of tumor relapse following primary debulking, and the development of chemoresistance. All these events are thought to be initiated and sustained by a subpopulation of neoplastic cells, termed ovarian cancer stem cells (OCSC), that are endowed with self-renewing and tumor-initiating properties. This implies that interfering with OCSC function should offer novel therapeu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…For example, gene MGP , a member of the osteocalcin/matrix Gla protein family, has been reported to drive stemness and tumor initiation in ovarian cancer. 62 Except for MGP , NDN , 63 SERP2 , 64 FSTL1 , 65 and CDH5 66 were also closely related to tumor stemness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, gene MGP , a member of the osteocalcin/matrix Gla protein family, has been reported to drive stemness and tumor initiation in ovarian cancer. 62 Except for MGP , NDN , 63 SERP2 , 64 FSTL1 , 65 and CDH5 66 were also closely related to tumor stemness.…”
Section: Discussionmentioning
confidence: 97%
“…Among 72 genes, consisting of 47‐GPS, 19 genes were differentially upregulated in high‐risk group, and most of them were associated with tumor stemness, and tumor initiation and metastasis (Table S4). For example, gene MGP , a member of the osteocalcin/matrix Gla protein family, has been reported to drive stemness and tumor initiation in ovarian cancer 62 . Except for MGP , NDN , 63 SERP2 , 64 FSTL1 , 65 and CDH5 66 were also closely related to tumor stemness.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the inactive form of MGP can be considered a marker for the assessment of vascular calcification [50]. Additionally, MGP is involved in a variety of cancers trough the overexpression of the MGP gene in breast cancer cells, in primary renal, testicular, and prostate carcinomas, in ovarian and digestive neoplasia, and in glioblastoma [2,3,33,38,[49][50][51][52][53].…”
Section: Vitamin K and Extrahepatic Vitamin K-dependent Proteinsmentioning
confidence: 99%
“…Ovarian cancer is the primary contributor to mortality among gynecological malignancies worldwide ( Chen et al, 2021 ), largely due to extensive dissemination to serosal surfaces and concurrent peritoneal metastasis ( Smolle, Taucher & Haybaeck, 2014 ; Nieddu et al, 2023 ; Zhang et al, 2022 ). However, the precise mechanisms underlying the metastatic progression of ovarian cancer remain poorly understood, highlighting a critical need to comprehend the molecular pathways implicated in disease development.…”
Section: Introductionmentioning
confidence: 99%